2019
DOI: 10.2478/jvetres-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of thrombocytes in Osteichthyes

Abstract: Thrombocytes in vertebrates other than mammals, inter alia in fish, are analogues of platelets in mammals. In Osteichthyes, these cells take part in haemostatic processes, including aggregation and release reactions in cases of blood vessel damage, and in the immune response development as well. This paper discusses the development of thrombocytes in Osteichthyes, taking into account the need to make changes to the concept of grouping progenitor cells as suggested in the literature. The following pages present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…Different thrombocyte shapes, including round, oval, oblong, and spindle-shaped, were observed in O. argus , which was consistent with the reports in other fish ( Fang et al, 2014 ; Gao et al, 2007b ; Michał, Beata & Wiesław, 2019 ; Rio-Zaragoza et al, 2011 ; Zhang et al, 2011 ; Zheng et al, 2016 ). The spindle-shaped thrombocytes often existed alone with some vacuoles in the cytoplasm and were related to cell phagocytosis ( Nagasawa, Somamoto & Nakao, 2015 ; Stosik et al, 2002 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Different thrombocyte shapes, including round, oval, oblong, and spindle-shaped, were observed in O. argus , which was consistent with the reports in other fish ( Fang et al, 2014 ; Gao et al, 2007b ; Michał, Beata & Wiesław, 2019 ; Rio-Zaragoza et al, 2011 ; Zhang et al, 2011 ; Zheng et al, 2016 ). The spindle-shaped thrombocytes often existed alone with some vacuoles in the cytoplasm and were related to cell phagocytosis ( Nagasawa, Somamoto & Nakao, 2015 ; Stosik et al, 2002 ).…”
Section: Discussionsupporting
confidence: 90%
“…These results were similar to those of the Murray cod ( Shigdar, Harford & Ward, 2009 ), tilapia ( Ueda et al, 2001 ), and piebald naked carp ( Zheng et al, 2016 ). The thrombocytes of lower vertebrates are functionally similar to platelets in mammals ( Michał, Beata & Wiesław, 2019 ), playing an important role in the process of hemostasis and coagulation ( Chen et al, 2018 ; Ferdous & Scott, 2015 ; Peng et al, 2018 ). Studies have investigated whether thrombocytes in some fish have phagocytotic abilities ( Da Silva et al., 2011 ; Michał, Beata & Wiesław, 2019 ; Shigdar et al, 2007 ; Shigdar, Harford & Ward, 2009 ; Tavares-Dias et al., 2007 ; Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In literature is reported that thrombocytes in fish, amphibians, reptiles and birds are analogues of platelets in mammals and also human (Stosik et al, 2019). The difference between fish and mammalian thrombocytes, including human is that fish thrombocytes are nucleated cells ( Fig.…”
Section: Thrombocytesmentioning
confidence: 99%
“…In fish, electron microscopy studies reveal a canalicular structure similar to human platelets and pseudopodia-like projections in aggregates (Carradice and Lieschke, 2008). Both human and fish thrombocytes have a major role in maintaining vascular integrity, hemostasis and in aggregation and release reactions in cases of blood vessel damage and in the immune response development (Thomas and Storey, 2015;Stosik et al, 2019). Moreover, it was discovered that Danio rerio thrombocytes function analogously to human platelets in adherence, secretion and aggregation (Carradice and Lieschke, 2008).…”
Section: Thrombocytesmentioning
confidence: 99%
“…Higher up the evolutionary chain, small nucleated thrombocytes with features similar to that of the mammalian platelet are present in species such as birds, reptiles, fish, and amphibians [ 8 , 9 ]. Not only do these nucleated thrombocytes play a role in coagulation [ 10 , 11 ], but, similar to mammalian platelets, have been shown to play significant roles in the immune responses of these organisms [ 9 , 12 , 13 ]. For example, avian thrombocytes and fish thrombocytes have been reported to possess functional toll like receptors that initiate immune responses to various pathogens, in addition to being able to phagocytose beads, viruses, and bacteria [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%